2020
DOI: 10.1186/s13287-020-01633-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells ameliorate myocardial fibrosis in diabetic cardiomyopathy via the secretion of prostaglandin E2

Abstract: Background: Diabetic cardiomyopathy (DCM) is a cardiac complication of long-term uncontrolled diabetes and is characterized by myocardial fibrosis and abnormal cardiac function. Mesenchymal stem cells (MSCs) are multipotent cells with immunoregulatory and secretory functions in diabetes and heart diseases. However, very few studies have focused on the effect and the underlying mechanism of MSCs on myocardial fibrosis in DCM. Therefore, we aimed to explore the therapeutic potential of MSCs in myocardial fibrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 32 publications
2
37
0
5
Order By: Relevance
“…Over the past few decades, transplantation of MSCs has shown promising results in MI recovery in animal studies and early clinical trials due to the availability of cells from numerous sources and the multilineage potential and immune privileged status of these cells. MSC infusion is reported to ameliorate cardiac fibrosis and dysfunction in diabetic cardiomyopathy rats [ 22 ]. Besides, MSCs are verified as an effective treatment in mitigating cardiac damage by promoting angiogenesis, decreasing the infiltration of immune cells and collagen deposition in diabetes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, transplantation of MSCs has shown promising results in MI recovery in animal studies and early clinical trials due to the availability of cells from numerous sources and the multilineage potential and immune privileged status of these cells. MSC infusion is reported to ameliorate cardiac fibrosis and dysfunction in diabetic cardiomyopathy rats [ 22 ]. Besides, MSCs are verified as an effective treatment in mitigating cardiac damage by promoting angiogenesis, decreasing the infiltration of immune cells and collagen deposition in diabetes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These processes prevent fibrosis by reducing collagen accumulation and consequently the fibrotic deposition of the extracellular matrix [ 132 ]. MSC effects have been also evaluated in a rat model of diabetic cardiomyopathy, in which uncontrolled diabetes was characterized by a long-term complication leading to myocardial fibrosis [ 133 ]. In this work, starting from the observation that PGE2 is secreted by MSCs during inflammation and immune response, the authors demonstrated the key role of this factor in fibrosis by using PGE2-deficient MSCs.…”
Section: Main Msc Priming Strategies To Enhance the Production Ofmentioning
confidence: 99%
“…При повреждении эти клетки трансформируются в фенотип миофибробластов и способствуют развитию фиброза миокарда и как следствие расширению камер сердца, гипертрофии кардиомиоцитов и апоптозу, что, в конечном итоге, приводит к прогрессированию СН [10,11]. В норме сердечные фибробласты поддерживают гомеостаз ЭЦМ, который обеспечивает структурную основу для кардиомиоцитов, распределяет механическую нагрузку по миокарду и проводит электрический потенциал [11,12]. При активации фибробластов биохимическими агентами разрушенных кардиомиоцитов и дефицитом кислорода происходит повышение экспрессии различных провоспалительных цитокинов и профибротических факторов.…”
Section: патологическая анатомия и физиология фиброза миокардаunclassified
“…Важно отметить, что фиброз миокарда коррелирует не только с тяжестью ХСН, но и с риском развития нарушений ритма и проводимости, а также повышает вероятность внезапной сердечной смерти [11]. Помимо ишемической болезни сердца к фибротическому ремоделированию миокарда могут приводить также артериальная гипертензия, сахарный диабет, метаболический синдром, врожденные и приобретённые пороки сердца и другие сопут ствующие патологии [7,12,13]. Метаанализ 1605 клинических исследований (Clinicaltrials.gov), посвященных поиску маркеров, ассоциированных с неблагоприятным течением ишемической болезни сердца, продемонстрировал, что только лишь 12,5% из них посвящены изучению маркеров с позиции патологического ремоделирования и фиброза миокарда [7,12,13].…”
unclassified
See 1 more Smart Citation